2013
DOI: 10.1002/eqe.2336
|View full text |Cite
|
Sign up to set email alerts
|

Modal analysis of pile‐supported structures during seismic liquefaction

Abstract: The purpose of this paper is to investigate the effects of liquefaction on modal parameters (frequency and damping) of pile-supported structures. Four physical models, consisting of two single piles and two 2 × 2 pile groups, were tested in a shaking table where the soil surrounding the pile liquefied because of seismic shaking. The experimental results showed that the natural frequency of pile-supported structures may decrease considerably owing to the loss of lateral support offered by the soil to the pile. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…Overall, the stiffness of the test system in Model 2 was relatively great than that in Model 1. Lombardi and Bhattacharya (2014) indicated that the natural frequency reduced by 20%-25% and 50%-60% at partial and full liquefaction, and the damping ratio increased by approximately 20% and 50% at partial and full liquefaction, respectively. The modal parameters of structure are listed in Table 1 at different stages of liquefaction.…”
Section: Assessment Of Modal Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the stiffness of the test system in Model 2 was relatively great than that in Model 1. Lombardi and Bhattacharya (2014) indicated that the natural frequency reduced by 20%-25% and 50%-60% at partial and full liquefaction, and the damping ratio increased by approximately 20% and 50% at partial and full liquefaction, respectively. The modal parameters of structure are listed in Table 1 at different stages of liquefaction.…”
Section: Assessment Of Modal Parametersmentioning
confidence: 99%
“…According to the experimental results, the modal parameters of the pile-superstructure were calculated before liquefaction and investigated based on the previous study (Lombardi and Bhattacharya, 2014) at partial and full liquefaction of the sand stratums. This was done because the experiments were not performed with a higher amplitude of white noise.…”
Section: Assessment Of Modal Parametersmentioning
confidence: 99%
“…The effects induced by soil liquefaction increase the damping ratio, which can reach values as high as 20% (Lombardi and Bhattacharya, 2014).…”
Section: Dampingmentioning
confidence: 99%
“…Ductility may be significantly lower in liquefaction conditions (Lombardi and Bhattacharya, 2014). Displacement ductility demand is defined as the ratio of global frame displacement demand to the yield displacement.…”
Section: Ductilitymentioning
confidence: 99%
“…Based on these structural parameters, the acceleration required for the assessment of the base shear force can be determined from an idealised acceleration response spectrum, such as the one depicted in Figure . In a conventional force‐based design, the effects induced by soil liquefaction, namely lengthening in period and increase in damping ratio, which can reach value as high as 20%, see for example , have significant consequences on the assessment of the seismic demand imposed by the shaking. Lombardi & Bhattacharya concluded that the pseudo‐acceleration, and consequently the base‐shear force, that the structure would experience during liquefaction condition may be significantly lower than that experienced prior to liquefaction condition (see Figure ).…”
Section: Introductionmentioning
confidence: 99%